Complete genome sequence of Cellulomonas flavigena type strain (134T). Issue 1 (July 2010) - Abt, Birte; Foster, Brian; Lapidus, Alla; Clum, Alicia; Sun, Hui; Pukall, Rüdiger; Lucas, Susan; Glavina Del Rio, Tijana; Nolan, Matt; Tice, Hope; Cheng, Jan-Fang; Pitluck, Sam; et al.
Abstract Cellulomonas flavigena (Kellerman and McBeth 1912) Bergeyet al. 1923 is the type species of the genusCellulomonas of the actinobacterial familyCellulomonadaceae . Members of the genusCellulomonas are of special interest for their ability to degrade cellulose and hemicellulose, particularly with regard to the use of biomass as an alternative energy source. Here we describe the features of this organism, together with the complete genome sequence, and annotation. This is the first complete genome sequence of a member of the genusCellulomonas, and next to the human pathogenTropheryma whipplei the second complete genome sequence within the actinobacterial familyCellulomonadaceae . The 4, 123, 179 bp long single replicon genome with its 3, 735 protein-coding and 53 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.